Estudio de la actividad del inhibidor de la fibrinólisis activable por trombina (TAFI), en plasma de pacientes con generación de trombina disminuida // Thrombin activatable fibrinolysis inhibitor (TAFI) activity in plasma from patients with diminished endogenous thrombin generation - D’Errico, María Lucía; Bosch, Norma; Ruiz-Saez, Arlette; Boadas, Apsara; Ibarra, Carlos; Salazar, Ana María; Guerrero, Belsy (Investigación Clínica, 2020)
Resumen El inhibidor de la fibrinólisis activable por trombina (TAFI), es una proteína de la hemostasia que enlaza la coagulación y la fibrinólisis. El objetivo de este estudio fue establecer condiciones para evaluar el TAFI activado (TAFIa), en plasma de pacientes con generación de trombina (GT) endógena disminuida. Se estudiaron plasmas de 36 controles y 28 pacientes con hemofilia A severa (HAS), 18 sin inhibidores y 10 con inhibidores anti-FVIII; a nivel basal y en respuesta al tratamiento con concentrados de FVIII recombinante y con FVII recombinante activado, respectivamente. Se evaluó el TAFIa por ensayos colorimétricos, con la adición en la mezcla de activación del sustrato 5nM hipuril-arginina y diferentes concentraciones de trombina en presencia de 8nM de trombomodulina. Los resultados evidenciaron a nivel basal, en relación a los controles en los plasmas de pacientes con HAS valores disminuidos de GT y de TAFIa (activado con 20 nM de trombina) y una correlación positiva entre ambos parámetros; luego del tratamiento, los valores fueron similares a los controles, con mejor y más duradera respuesta en los pacientes sin inhibidores. Los valores de TAFIa a nivel basal en el plasma de pacientes con HAS, se normalizaron cuando se activó con concentraciones de trombina mayores o iguales a 120 nM. En conclusión, para estudiar TAFIa en plasma de pacientes con alteraciones de la coagulación asociadas a baja GT, en el ensayo se deben evaluar diversas concentraciones de trombina, para diferenciar una actividad de TAFIa disminuida de una incompleta activación, como lo observado en el plasma de pacientes con HAS. Abstract Thrombin activatable fibrinolysis inhibitor (TAFI) is a hemostasis protein that acts as a link between coagulation and fibrinolysis. The aim of this study was to establish the conditions to evaluate the TAFI activity (TAFIa) in the plasma of patients with diminished endogenous thrombin generation (GT). The plasmas from 36 controls and 28 patients with severe hemophilia A (HAS, 18 without inhibitors and 10 with anti-FVIII inhibitors, treated on-demand with recombinant factor VIII concentrates and with recombinant activated factor VII, respectively) were studied, at baseline and in response to treatment. TAFIa was evaluated by colorimetric tests, being the most relevant modifications, the addition in the activation mixture of 5nM hypuril-arginine as substrate and different thrombin concentrations in the presence of 8nM thrombomodulin. The results showed that the plasma of patients, in relation to controls, have a decreased GT and TAFIa (using 20 nM thrombin as activator) at baseline, and a positive correlation between both parameters. After treatment, the values were similar to the controls, occurring the best and most lasting response in those patients without inhibitors. At baseline, TAFIa values in the plasma of HAS patients were normalized when ≥ 120 nM thrombin concentrations were used as activator. In conclusion, to study TAFIa in the plasma of patients with coagulation abnormalities associated to a low GT, diverse thrombin concentrations should be evaluated, in order to differentiate a diminished TAFIa from an incomplete zymogen activation, as observed in the plasma of patients with HAS.